Biotreatment of Industrial Pollutant (Carbon Dioxide) and its Role in Bioplastics Production - Gatea, Iman H.; Sabei, Ansam S.; Abbas, Adnan H.; Tawfeeq, Rana F.; Abid, Ameena G.; Sabr, Adawiya B. (Journal of Petroleum Research and Studies, 2024)
Polyhydroxyalkanoates (PHAs) are a class of biopolymers with characteristics resembling those of petrochemical-based plastics that have gained recent attention and a growing amount of research effort due to their environmental friendliness. Numerous bacteria, including Alcaligenes spp., Pseudomonas spp., Staphylococcus spp., and algae create (PHAs) in the presence of carbon and limiting nutrients like nitrogen, and these biopolymers can successfully replace industrial plastics. Therefore, the goal of this study is to employ carbon dioxide, an industrial pollutant emitted into the environment, as a cheap carbon source to lower production costs and remove pollution at the same time. Only three of the nine bacterial isolates utilized were able to synthesize the polymer in the presence of CO2, and the best isolate was belonging to the genus Alcaligenes after 48 hours of incubation at 30°C and pH 7, which are the optimal conditions for polymer synthesis. Bacterial growth resulted in the production of 5.2gm/l of PHA and 6.2gm/l of biomass under these conditions.